Ασφάλεια και προστασία της ιδιωτικότητας στο διαδικτύο - Σπυριδωνίδου, Κωνσταντίνα (Εθνικό Εθνικό Μετσόβιο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2015)
The Web has spurred an information revolution even, reaching sectors left untouched by the personal computing boom of the 80’s. It made information ubiquity a reality for sizeable segments of the world population, transcending all socioeconomic levels. The ease of information access, coupled with the availability of personal data, also made it easier and more tempting for interested parties (individuals, businesses, and governments) to intrude on people’s privacy in unprecedented wayslevels. Internet privacy involves the right of personal privacy concerning the storing, repurposing, provision to third parties, and displaying of information pertaining to oneself via the Internet. Internet privacy is a subset of computer privacy. Although we recognize that many and different levels of privacy violations exist, the present study is analyzing the internet privacy from user’s perspectives focusing on its preservation or loss. Internet users’ privacy can be violated in different ways and with different intentions.Unauthorized information transfer, weak security, data magnets (cookies, software downloads etc.), and indirect forms of information collection are some of them. However, internet users on their vast majority tend to neglect or overlook the privacy settings and over-share data that can be easily either stolen or used in many ways against them as there are parties who would use these data in their favor. This is easily perceptible through social media where users share their whole life believing that it is protected. As far as the programmers and the managers of the information systems, they must take into account the appropriate privacy enhancing technologies in order to provide privacy and protection to the internet user, considering that the legislative measures are not sufficient.